Modern mosques in Malaysia between regionalism and eclecticism - Mousa, Wael A. Yousef (Penerbit Universiti Sains Malaysia, 2014)
This richly illustrated book introduces readers, through a thoughtful critical analysis, to a unique blend selected modern mosques in Malaysia.